2006
DOI: 10.1055/s-2006-950056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aqueous garlic extract on oxidant/antioxidant status in 32 D and 32 Dp cell lines

Abstract: Aim:To investigate the possible effects of aqueous garlic extract on the oxidant/antioxidant status and apoptosis in 32D (wild type mouse myeloid cell = normal) and 32Dp210 (BCR-ABL fusion gene (+) mouse myeloid cell = Chronic Myelocytic Leukemia cells) cell lines. Materials and methods:Aqueous garlic extract (10% w/v) was added into the cell line media with 2 different final concentrations (0.4% and 1%). At 0 h and at 24, 48, and 72 h later, the oxidant (malondialdehyde (MDA) level, and xanthine oxidase (XO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Our findings suggested that oxidant potential of the garlic extract which was created by increased xanthine oxidase activity and/or its own ingredients might play an important role in the anticancer property of garlic. This property of garlic was supposed to be a potential chemo-preventive force in chronic myeloid leukemia [22,23]. In another study, it was concluded that DATS-induced ROS generation in human prostate cancer cells was mediated by an increase in labile iron due to the degradation of ferritin [24].…”
Section: Cell Line Studiesmentioning
confidence: 98%
“…Our findings suggested that oxidant potential of the garlic extract which was created by increased xanthine oxidase activity and/or its own ingredients might play an important role in the anticancer property of garlic. This property of garlic was supposed to be a potential chemo-preventive force in chronic myeloid leukemia [22,23]. In another study, it was concluded that DATS-induced ROS generation in human prostate cancer cells was mediated by an increase in labile iron due to the degradation of ferritin [24].…”
Section: Cell Line Studiesmentioning
confidence: 98%
“…It was also found that urinary frequency and international prostate symptom score values decreased, maximum, and average rates of urine flow increased after the extract consumption. Among the major organosulfur compounds of garlic, diallyl sulfide indicated antioxidant potential against testosterone-induced oxidative stress in prostate of Swiss albino mice (Prasad et al, 2006) and aged garlic extract created oxidant stress, which was reflected by significant increases in malondialdehyde level and xanthine oxidase enzyme activity in 32Dp210 cells (Durak et al, 2006). Considering all of these, garlic and its derivatives have antioxidant properties, which are supposed to affect the improvement of BPH.…”
mentioning
confidence: 99%